The Calcium-Activated Chloride Channel TMEM16A is Inhibitied by Liquiritigenin - Kato, Mami; Takayama, Yasunori; Sunagawa, Masataka (Frontiers in Pharmacology, 2021)
The transmembrane 16 (TMEM16) family contains 10 subtypes, and the function of each protein is different. TMEM16A is a calcium-activated chloride channel involved in physiological and pathological situations. Liquiritigenin is an aglycone derived from Glycyrrhiza glabra, and it is generated via the metabolism of enterobacterial flora. It has been known that liquiritigenin reduces pain sensation involving TMEM16A activation in primary sensory neurons. In addition, other pharmacological effects of liquiritigenin in physiological functions involving TMEM16A have been reported. However, the relationship between TMEM16A and liquiritigenin is still unknown. Therefore, we hypothesized that TMEM16A is inhibited by liquiritigenin. To confirm this hypothesis, we investigated the effect of liquiritigenin on TMEM16A currents evoked by intracellular free calcium in HEK293T cells transfected with TMEM16A. In this study, we found that liquiritigenin inhibited the mouse and human TMEM16A currents. To further confirm its selectivity, we also investigated its pharmacological effects on other ion channels, including transient receptor potential vanilloid 1 (TRPV1) and ankyrin 1 (TRPA1), which are non-selective cation channels involved in pain sensation. However, liquiritigenin did not inhibit the currents of TRPV1 and TRPA1 induced by capsaicin and allyl isothiocyanate, respectively. Therefore, our findings indicate that selective TMEM16A inhibition could be one molecular mechanism that explains liquiritigenin-induced pain reduction. Additionally, we also investigated the inhibitory effects of estrogens on TMEM16A because liquiritigenin reportedly binds to the estrogen receptor. In this study, a pregnancy-dependent estrogen, estriol, significantly inhibited TMEM16A. However, the efficacy was weak. Although there is a possibility that TMEM16A activity could be suppressed during pregnancy, the physiological significance seems to be small. Thus, the inhibitory effect of estrogen might not be significant under physiological conditions. Furthermore, we investigated the effect of dihydrodaidzein, which is an analog of liquiritigenin that has a hydroxyphenyl at different carbon atom of pyranose. Dihydrodaidzein also inhibited mouse and human TMEM16A. However, the inhibitory effects were weaker than those of liquiritigenin. This suggests that the efficacy of TMEM16A antagonists depends on the hydroxyl group positions. Our finding of liquiritigenin-dependent TMEM16A inhibition could connect the current fragmented knowledge of the physiological and pathological mechanisms involving TMEM16A and liquiritigenin.